Shopee's E-Commerce Marketing Strategy in International Business - Mela Devita; Zuhrinal M Nawawi; Nuri Aslami (Journal Of Social Research, 2021)
The lifestyle of modern society and economy has been shaped by the advancement and evolution of information technology. Shopee implements worldwide marketing strategies to achieve success in foreign businesses, due to the high number of internet users and the desire to shop online. This study uses a descriptive approach and uses a qualitative strategy. Secondary data were collected through literature review found in various materials, including scientific journals and novels. The purpose of this research is to find out how Shopee's marketing approach has developed and grown in foreign markets. According to the findings of this study, Shopee uses a combination of techniques, including a pull approach and a push strategy, to increase consumer loyalty. Shopee has launched Shopee Streamer Academy, a new curriculum. Shopee's new program is a one of a kind marketing public relations approach to influencing public perception, which benefits the company's sales.